Response Mechanism of Endogenous Hormones of Potential Storage Root to Phosphorus and Its Relationship With Yield and Appearance Quality of Sweetpotato - Si, Cheng-cheng; Liang, Qing-gan; Liu, Hong-Juan; Wang, Ning; Kumar, Sunjeet; Chen, Yan-li; Zhu, Guo-peng (Frontiers in Plant Science, 2022)
Field and pot experiments under five rates of phosphorus were conducted to explore the response mechanism of endogenous hormones of potential storage root to phosphorus and its relationship with yield and appearance quality of sweetpotato. Compared with the control, proper phosphorus application (P2, 112 kg P2O5 ha-1 in field experiment or 0.04 g P2O5 kg-1 in pot experiment) improved the yield and appearance quality of sweet potato. Probably because, P2 treatment significantly increased the expression of Ibkn1 and APRT, and the concentration of ZR from 20 to 40 days after planting, but the results were the opposite at 10 days after planting. And, increased in the expression of SRD1, NIT4, IbMADS1, and OPR3, and the concentrations of IAA and JA from day 10 to 40 after planting were observed. Furthermore, expression of GA3oX4 and concentration of GA3 decreased significantly from 20 to 30 days of planting, and significantly increased after 40 days of planting. Moreover, a significant decrease in the expression of AAO and concentration of ABA were observed from 10 to 30 days after planting, and significant increase were observed after 40 days of planting. As a result, P2 treatment promoted root development, especially significantly increased the number of root and potential storage root. P2 treatment significantly increased the diameter, weight, and number of storage root at 40 days after planting. Finally, proper phosphorus application (112 kg P2O5 ha-1) increased the yield (increment 18.99% to 25.93%) by increasing the storage roots number per plant, improved appearance quality by increasing the length/diameter ratio and uniformity weight of storage root.